Exploring Ecojustice & Environmental Learning through Online Preservice Teacher Education - Sperling, Erin; Inwood, Hilary; Sims, Laura; Elliott, Paul (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
As teacher education can help communities transition to sustainable, just ways of being, this study reports on the development of, and research on, a national E-course for preservice teachers focused on Environmental and Sustainability Education (ESE). This collaborative initiative brought together academics, community educators, and K-12 teachers to offer participatory, locally-relevant online ESE learning. By facilitating learning centred on concepts of indigenization, ecojustice, and place-based learning, the E-course aimed to ensure equitable access to ESE for preservice teachers across Canada. We ask, what are participants’ experiences and the impact of their involvement in this E-course? Using a socio-critical lens, the authors draw on survey data to report on the outcomes of the E-course. We hope that it may serve as a new model for online ESE for preservice teacher education, and more broadly highlight the capacity for building understanding about ecojustice education and community connections through virtual learning spaces.